Adopting Moderate Alcohol Consumption in Middle-age: Subsequent Cardiovascular Events - King, Dana E. (2008)
PURPOSE: Moderate alcohol use is part of a healthy lifestyle, yet current guidelines caution non-drinkers against starting to drink alcohol in middle-age. The purpose of this study was to evaluate whether adopting moderate alcohol consumption in middle-age would result in subsequent lower cardiovascular risk. METHODS: This study examined a cohort of adults age 45-64 participating in the Atherosclerosis Risk in Communities (ARIC) study over a 10 year period. The primary outcome was fatal or non-fatal cardiovascular events. RESULTS: Of 7,697 participants who had no history of cardiovascular disease and were non-drinkers at baseline, within a 6 year follow-up period 6.0% began moderate alcohol consumption (2 drinks per day or fewer for men, 1 drink per day or fewer for women) and 0.4% began heavier drinking. After 4 years of follow up, new moderate drinkers had a 38% lower chance of developing cardiovascular disease than did their persistently non-drinking counterparts. This difference persisted after adjustment for demographic and cardiovascular risk factors (OR 0.62, 95% confidence interval [CI] 0.40-0.95). There was no difference in all-cause mortality between the new drinkers and persistent non-drinkers (OR 0.71, CI 0.31-1.64). CONCLUSION: People who newly begin consuming alcohol in middle-age rarely do so beyond recommended amounts. Those who begin drinking moderately experience a relatively prompt benefit of lower rates of cardiovascular disease morbidity with no change in mortality rates after 4 years.